Effect of Functional Electrical Stimulation on Improving Upper Extremity Motor Function in Stroke Patients Revealed by fMRI:a Controlled Study - Fangfang ZHENG; Huihua LIU; Tiebin YAN; Xiaokun JIN; Xiaohui DUAN; Jun SHEN (康复学报)
Objective:To investigate the effect of functional electrical stimulation (FES) on brain function by using functional magnetic resonance imaging (fMRI), and further explore the mechanism of FES on central nervous system rehabilitation in patients with sub-cortical stroke.Methods:Ten subjects were recruited in the study, including five stroke patients (stroke group) and five age-and-gender-matched healthy persons (control group). While the stroke group received FES on the affected wrist extensors and thumb abductors, the control group accepted FES on the same muscles in the left hand, and wrist extension and thumb abduction were induced by FES.Simutaneously, fMRI scans were conducted and the whole brain functional images were recorded.SPM2 was used to analyze image, the brain activation maps were acquired during attempted motor tasks in both groups, the active intensity and range of sensorimotor cortex (SMC) between two groups were compared. Laterality indexes (LIs) were also calculated and the relationship of LIs and upper extremity function recovery was investigated.Results:Besides contralateral premotor cortex (PMC), inferior parietal lobule (IPL), cingulate motor area (CMA) and cerebellum (CRB), contralateral SMC was mainly activated by FES in control group. However, subjects with stroke activated more ipsilateral area including ipsilateral SMC, IPL etc. Although no significant differences were found between groups for the range and intensity of bilateral SMC, enhanced activation of ipsilateral SMC was observed in stroke group, and a positive relationship between LIs and Fugl-Meyer scores of upper extremity in stroke group was observed.Conclusions:FES can activate brain areas related to sensation and movement through sensory inputs and passive movements, which may be one of the mechanisms of FES on improving limb function in patients with subcortical stroke.